2022
DOI: 10.1116/6.0002122
|View full text |Cite
|
Sign up to set email alerts
|

Time response measurement of pulsed electron beam from InGaN photocathode

Abstract: The photocurrent from a semiconductor photocathode with a negative-electron affinity surface can be arbitrarily controlled by the excitation laser power. Applying this characteristic to a scanning electron microscope allows the probe current to be arbitrarily controlled at any location on the sample. A photocathode with a fast time response is required to control the probe current at high speed. This study used an InGaN photocathode for pulsed electron beam generation and investigated its time response. A puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…These dopants, such as indium (In) or phosphorous (P) can decrease the E gap to a more suitable wavelength in the visible spectral range and recently published studies reported on the potential usage of such novel InGaN photocathodes. [157][158][159] 5.4.2 Preparation. The commercially available semiconductor undergoes a wet-chemical cleaning before being installed in a UHV chamber.…”
Section: Gallium Nitridementioning
confidence: 92%
See 1 more Smart Citation
“…These dopants, such as indium (In) or phosphorous (P) can decrease the E gap to a more suitable wavelength in the visible spectral range and recently published studies reported on the potential usage of such novel InGaN photocathodes. [157][158][159] 5.4.2 Preparation. The commercially available semiconductor undergoes a wet-chemical cleaning before being installed in a UHV chamber.…”
Section: Gallium Nitridementioning
confidence: 92%
“…These dopants, such as indium (In) or phosphorous (P) can decrease the E gap to a more suitable wavelength in the visible spectral range and recently published studies reported on the potential usage of such novel InGaN photocathodes. 157–159…”
Section: Semiconductor Photocathodesmentioning
confidence: 99%
“…Furthermore, we focused on GaN-based semiconductors, which are wide bandgap semiconductors with the advantage of larger surface band bending (φBB) than that of a GaAs semiconductor and achieved 20 times longer lifetime [9]. Further developed InGaN semiconductor photocathodes using GaN-based semiconductor materials have achieved electron emission with energy dispersion below 0.1 eV, current density exceeding 1 kA/cm 2 , and generation of pulsed electron beams with a rise time of 1.5 ns consistent with the temporal structure of the irradiated pulsed laser [10], [11].…”
Section: Photoelectron Beams From Semiconductor Photocathodementioning
confidence: 95%
“…2), the probe current can be selectively changed within one field of view of the SEM image. [1][2][3] This technology is called Digital Selective e-Beaming (DSeB). DSeB is implemented by synchronizing the laser output signal that irradiates the photocathode with the SEM scan signal (Fig.…”
Section: Vc Change Of Nmos Due To Selective E-beam Irradiationmentioning
confidence: 99%